On the Limitations and Promise of Quantum Theory for Comprehension of Human Knowledge and Consciousness - Helrich, Carl S. (2006)
Abstract. I present a partially historical discussion of the basis of the quantum theory in nonmathematical terms using human knowledge and consciousness as an underlying theme. I show that the philosophical position in both classical and quantum theory is the experimental and mathematical philosophy of Isaac Newton. Because almost all the systems we deal with are multicomponent, we must consider the limitations and openness imposed by thermodynamics on our claims in both classical and quantum treatments. Here the reality of measurement stands in the way of any simple picture but also provides the basis for considerations of free will. Particular care is taken with the concepts of quantum measurement, entanglement, and decoherence because of their importance in the discussion.
Keywords: Measurement; Information theory; human knowledge; Experiment; Consciousness; classical and quantum theory